IMPLEMENTASI ALGORITMA SMITH PADA APLIKASI ISTILAH TEKNIK INDUSTRI KIMIA - Nasib Marbun; Ahmad Riza Fuadi; Muasir Pagan; Suranta Bill Fatric Ginting; Muhammad Zarlis; Dedy Hartama (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2019)
Companies engaged in the chemical industry really need Human Resources (HR) who have knowledge in the field of chemical industry engineering terms in order to achieve the company's main goals, but due to the chemical industry engineering terms that use foreign languages is essentially difficult to understand not a few of the general public who have desire to work in companies in the chemical industry engineering experience problems in mastering the knowledge needed by chemical industry engineering companies. Therefore it is necessary to have an application that adopts science related to the chemical industry engineering term along with good search features. The application that was built to search for information related to chemical industry engineering terms in this study implements the smith algorithm as an algorithm that serves to minimize the use of the time needed in the search process. The smith algorithm notices that counting the number of shifts with the text character that is located right next to the window character on the rightmost text can sometimes provide a shorter shift than using the rightmost window text character. Then he gives a solution to take the maximum between the two values. The application term of chemical industry engineering research was built using visual basic net 2008 and can be operated properly on personal computers supported by Windows OS. Keywords: Chemical Industry Engineering Terms, String Matching, Algorithms, Smith.